The Language Ambiguity in English Literature a 2024 Class at State University of Medan - Juan Barus; Meliana Napitu; Dinda Sabrina; Valendeo Pangaribuan; Muhammad Natsir (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2025)
The topic of this research is language ambiguity that is often spoken by every student in English Literature A class of 2024 at Medan State University. This research aims to answer "what types of language ambiguity are often spoken by students in their communication on everyday classes?". This research applies Kent Bach's theory of language ambiguity to answer this question, this theory is relevant to help this research. The method used in this research is qualitative research and also observation to each suspect in daily life in the classroom. To clarify what kind of language ambiguity is often spoken in the daily life of English Literature A students class of 2024, the researcher provides some sentences that look and sound "ambiguous" that have been spoken by students in their daily life in class. The results of this study are expected to provide new insights into how language ambiguity is used, either consciously or unconsciously, in students' daily interactions.